PENGARUH RELATED PARTY TRANSACTION DAN THIN CAPITALIZATION TERHADAP STRATEGI PENGHINDARAN PAJAK - Sapta Setia Darma (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2019)
To determine the effect of related party transactions and thin capitalization on tax avoidance strategy is goals of this study. This research was conducted within the scope of manufacturing companies listed on the Indonesia Stock Exchange (BEI) that published their financial statements during the period 2012-2016 with using purposive sampling as sampling method.  The analytical method used in this study are  classic assumption test and  multiple linear regression. Based on the test results it was found that the Related Party Transaction-Receivable, Related Party Transaction-Liability did not affect the effective tax rate. But the variables of thin capitalization, company size (size), and profitability affect the effective tax rate. This research  is expected can be useful for management in decision making to tax avoidance strategies.